2012
DOI: 10.1007/s00449-012-0820-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization, purification and characterization of novel thermostable, haloalkaline, solvent stable protease from Bacillus halodurans CAS6 using marine shellfish wastes: a potential additive for detergent and antioxidant synthesis

Abstract: A protease producing marine bacterium, Bacillus halodurans CAS6 isolated from marine sediments, was found to produce higher enzyme by utilizing shrimp shell powder. Optimum culture conditions for protease production were 50 °C, pH 9.0, 30 % NaCl and 1 % shrimp shell powder (SSP) and the protease purified with a specific activity of 509.84 U/mg. The enzyme retained 100 % of its original activity even at 70 °C, pH 10.0 and 30 % NaCl for 1 h. The purified protease exhibited higher stability when treated with ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 31 publications
8
21
0
1
Order By: Relevance
“…The highest IC 50 (1.4 mg/ml) was obtained with B. cereus SV1 hydrolysate [19]. Similarly Annamalai et al [37] reported that, the alkaline protease from B. halodurans CAS6 had attained 96 % maximum antioxidant activity using shrimp shell as a substrate. From the results obtained, it may be inferred that the reducing power of shrimp shell hydrolysate increased with increasing concentrations of samples (0.25-2 mg/ml).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The highest IC 50 (1.4 mg/ml) was obtained with B. cereus SV1 hydrolysate [19]. Similarly Annamalai et al [37] reported that, the alkaline protease from B. halodurans CAS6 had attained 96 % maximum antioxidant activity using shrimp shell as a substrate. From the results obtained, it may be inferred that the reducing power of shrimp shell hydrolysate increased with increasing concentrations of samples (0.25-2 mg/ml).…”
Section: Resultsmentioning
confidence: 89%
“…Similar to the present investigations, alkaline serine protease from various Bacillus sp. showed better blood cleaning ability [7,21,37,38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triton X‐100 is a non‐ionic surfactant, and it can improve the solubilization of the enzyme from the solid substrate to the solution. Sodium chloride was used to increase the stability of the enzyme, based on literature . Subsequently, the extract was filtered through a nylon net and the liquid fraction was centrifuged at 6000 × g for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Isolated protease has shown good stability and compatibility in the presence of detergent Surf excel. The enzyme retained more than 60% activity with most of the detergents tested even after 2.5 h incubation at 45°C after the supplementation of CaCl 2 and glycine (Annamalai et al, 2013). High activity alkaline protease was reported from Conidiobolus coronatus showing compatibility at 50°C, in the presence of 25 mM CaCl 2 , with a variety of commercial detergents.…”
Section: Compatibility With Detergentsmentioning
confidence: 90%